(untitled) (CIPEEX, 2023)
In this study, a considerable rate of absenteeism due to illness was evidenced among the employees of the Luziânia District - GO. The importance of health for the proper functioning of the Goian Judiciary is highlighted, as the lack of adequate care negatively affects the performance of their work activities. The research highlights the relevance of constitutional regulations, such as fundamental rights and the right to health, and also emphasizes the need for care regarding health-related changes, especially those related to modernization, and their impact on the employees. The results indicate the need to improve health care for public servants, with a focus on mental health, taking into account environmental, social, and technological factors. This research paves the way for broader investigations on how the management of the Judiciary can ensure the quality of life of its employees in accordance with the fundamental right to health.